An Analysis of the Adoption and Implementation of A Sugar-Sweetened Beverage Tax in South Africa: A Multiple Streams Approach - Petronell Kruger; Safura Abdool Karim; Aviva Tugendhaft; Susan Goldstein (Taylor & Francis Group, 2021)
This paper describes a case study of the adoption and implementation of the sugar-sweetened beverage tax in South Africa, termed the Health Promotion Levy. Qualitative data extraction and analysis of institutional documents, such as policy proposals and parliamentary debate records, stakeholder submissions to Parliament and media reports, were guided by the Kingdon Multiple Streams Theory as adapted to study agenda setting, policy adoption, and implementation. We present the following key findings: First, consistent messaging from policy entrepreneurs, consisting of advocacy groups, health organizations, and research entities, was key to ensuring that a tax policy solution was proposed and passed. Second, the continuity of certain key policymakers contributed to the relatively expedient passage of the tax policy. Third, the use of an excise tax was, amongst others, an appealing policy solution because of its revenue-raising potential; however, uncertainty regarding the purpose of the tax negatively impacted public attitudes toward it. Fourth, industry arguments, relating to unemployment, were effective in restructuring the tax in favor of industry actors. Finally, regulatory action by sectors outside of finance and health impacted stakeholder perceptions of the tax and possibly obstructed regular annual adjustments for inflation.